PENGEMBANGAN MODEL PEMBELAJARAN PKN BERBASIS COMPUTER ASSISTED INSTRUCTION UNTUK KESETARAAN PAKET C DI PKMB ENGGANG GADING PONTIANAK - Rusianto, Eddy; Astuti, Indri; Usman, Andy (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe abstract thing, rote and counting are the fundamental things that become the difficulties in understanding the PKn for the students. Thus it requires learning media in the form of Computer Assisted Instruction to help the students improving their skill in PKn learning process and the PKn learning result especially on the stoichiometry subject. This study aimed to produce the design, the final product, the implementation, and the result of Computer Assisted Instruction in PKn learning at kelas XII paket C di PKBM Enggang Gading Pontianak. This study was a tiered training media development study by using the development stage of Borg and Gall, with the subject of study was the class XII students consist of 25 students. The number of students who passed the test was increased in the posstest result taken after the learning process by using Computer Assisted Instruction which was showed that 80,4% students passed the test and only 50,2% students did not pass the test. It means that there were differences in learning outcomes between learning PKn by using Computer Assisted Instruction and not. Thus a tiered training media in PKnlearning could help the students to learn PKn material easily.Key Words: Pengembangan, Computer Assisted Instruction, PKn Â